2022
DOI: 10.1007/s11002-021-09601-8
|View full text |Cite
|
Sign up to set email alerts
|

Using virtual reality to increase charitable donations

Abstract: Marketer interest in using virtual reality (VR) as a persuasion tactic continues to rise. Notably, one sector at the forefront of utilizing this tactic for persuasive means is nonprofit marketing. Many charities have devoted considerable resources to creating VR appeals under the assumption that this medium will increase donations over and above present tactics. However, research has not yet examined the persuasive consequences VR may provide over more traditional channels. This research seeks to understand th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
2
8
1
Order By: Relevance
“…On the topic of augmented reality and its role in advertising, Pozharliev et al (2022) investigate whether augmented reality advertisements enhance customer physiological responses and to pay more than traditional print advertising by creating greater consumer arousal and engagement. This paper ties in nicely with the paper by Kristofferson et al (2022) in the first thematic section of the current issue that provides converging evidence in the context of charitable giving and shows virtual reality can also increase donations by consumers. The third paper in this thematic compilation on Consumer Preferences for and Reactions to AI and Other Emerging Technologies is by Choi et al (2022).…”
supporting
confidence: 61%
See 1 more Smart Citation
“…On the topic of augmented reality and its role in advertising, Pozharliev et al (2022) investigate whether augmented reality advertisements enhance customer physiological responses and to pay more than traditional print advertising by creating greater consumer arousal and engagement. This paper ties in nicely with the paper by Kristofferson et al (2022) in the first thematic section of the current issue that provides converging evidence in the context of charitable giving and shows virtual reality can also increase donations by consumers. The third paper in this thematic compilation on Consumer Preferences for and Reactions to AI and Other Emerging Technologies is by Choi et al (2022).…”
supporting
confidence: 61%
“…Thus, while the first two papers in this compilation look at how firm and individual consumer actions benefit society, this paper looks at how conferring individual level consumption with sociality benefits can increase the happiness such products provide to consumers. Finally, Kristofferson et al (2022) investigate the important role virtual reality can play in increasing charitable donations by consumers.…”
mentioning
confidence: 99%
“…In addition, Skadberg and Kimmel (2004) found support for the relationship between enjoyment and telepresence as variables affecting flow in the human-computer interaction. Kristofferson et al (2022) found that VR generated significantly higher donations when compared to a traditional 2D advertisement, which indicates that VR appeals can elicit increased donations.…”
Section: Charitable Giving and Vrmentioning
confidence: 86%
“…Kristofferson et al (2022) found that VR generated significantly higher donations when compared to a traditional 2D advertisement, which indicates that VR appeals can elicit increased donations. However, between donations to humans and animals, their results show that the donation amounts toward the animal, when compared to humans, are less.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the deployment of avatars and the utilization of rich new media formats (e.g., AR and VR) summon investigations into how these might be leveraged by brands to communicate with consumers. For example, although some research has begun to examine the use of AR and VR in standalone advertising contexts (Fritz et al, 2023a; Kristofferson et al, 2022), consumer responses may differ when such content is integrated within a broader Metaversal experience. Researchers may explore these potential avenues to help develop a nuanced understanding of how consumers respond to new communication formats in the Metaverse.…”
Section: The Consumer Journey Through the Metaverse: A Guide For Futu...mentioning
confidence: 99%